Aqueous dune-like bedforms in Athabasca Valles and neighbouring locations utilized in palaeoflood reconstruction. (15th November 2017) - Durrant, L.; Balme, M.R.; Carling, P.A.; Grindrod, P.M.
Abstract: Putative fluvial dunes have been identified within the Athabasca Valles and associated network of channels on Mars. Previous published work identified and measured bedforms in Athabasca Valles using photoclinometry methods on 2–3 m/pixel resolution Mars Orbiter Camera Narrow Angle images, and argued that these were created by an aqueous megaflood that occurred between 2 and 8 million years ago. This event is likely to have occurred due to geological activity associated with the Cerberus Fossae fracture system at the source of Athabasca Vallis. The present study has used higher resolution, 25 cm/pixel images from the Mars Reconnaissance Orbiter HiRISE camera, as well as stereo-derived digital terrain models and GIS software, to re-measure and evaluate these bedforms together with data from newly discovered neighbouring fields of bedforms. The analysis indicates that the bedforms are aqueous dunes, in that they occur in channel locations where dunes would be expected to be preserved and moreover they have geometries very similar to megaflood dunes on Earth. Dune geometries are used to estimate megaflood discharge rates, including uncertainty, which results support previous flood estimates that indicate that a flood with a discharge of ∼2 × 10 6 m 3 s −1 created these bedforms. Highlights: Athabasca Valles bedforms have similar geometries to megaflood Earth aqueous dunes. Earth-based dune height-length quantitative predictors fit well to Mars dunes. Discharge estimates indicate a 2 million m 3 s −1 megaflood deposited the dunes.